2010
DOI: 10.1177/1352458510389219
|View full text |Cite
|
Sign up to set email alerts
|

A functional magnetic resonance proof of concept pilot trial of cognitive rehabilitation in multiple sclerosis

Abstract: The results of the present study indicate that this cognitive rehabilitation programme increases brain activity in the cerebellum of cognitively impaired patients with MS. The role of fMRI in the assessment of neurorehabilitation schemes warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 52 publications
3
71
4
2
Order By: Relevance
“…The majority of these studies (N=5) used active fMRI imaging paradigms even if they are markedly influenced by individual task performance; more recently three studies 31,32,48 have used a resting-state fMRI approach to explore changes in functional connectivity. One of the first task-based studies was carried out by Sastre-Garriga et al 25 to investigate the effect on brain activity of a cognitive rehabilitation programme during the execution of the PASAT test. After rehabilitation, patients showed increased brain fMRI response only in the cerebellum when compared with healthy subjects.…”
Section: Imagingmentioning
confidence: 99%
“…The majority of these studies (N=5) used active fMRI imaging paradigms even if they are markedly influenced by individual task performance; more recently three studies 31,32,48 have used a resting-state fMRI approach to explore changes in functional connectivity. One of the first task-based studies was carried out by Sastre-Garriga et al 25 to investigate the effect on brain activity of a cognitive rehabilitation programme during the execution of the PASAT test. After rehabilitation, patients showed increased brain fMRI response only in the cerebellum when compared with healthy subjects.…”
Section: Imagingmentioning
confidence: 99%
“…Moreover, patients showed an improved performances in backward version of digit-span. Nevertheless, the authors did not find significant correlation between clinical and fMRI variations, likely because the small size of the sample [73].…”
Section: Cognitive Rehabilitationmentioning
confidence: 90%
“…Besides additional recruitment of brain regions, these studies reported increased brain activation in task-related areas. [9][10][11] Thus, the conclusion of all these studies was that spontaneous and induced functional reorganization takes place in MS. Given that the described findings were related to task performance, those changes were in line with our concept of 'adaptive' brain changes describing the brain's ability to adapt to brain injury, to counteract functional decline and to overcome disability.…”
Section: Iris-katharina Penner and Orhan Aktasmentioning
confidence: 99%